Russian Second-Language Textbooks and Identity in the Universe of Discourse A Contribution to Macropragmatics - Mladenova, Olga (Slavistische Beitraege, 2004)
This book provides an overview of the modifications and interaction of the Second-Language Learning discursive formation and the Identity discursive formation over four centuries of Russian history. It proposes an explanatory model in which small-scale linguistic detail is combined harmoniously with larger-scale language units in order to illuminate matters of cultural importance in their linguistic guise. Hallmark of its interdisciplinary scope is the isomorphic interpretation of image and text. Compositionally, interdisciplinarity pours into a nonlinear narrative; this narrative follows a spiral, redefining on a higher level and in a different setting distinctions, which were first discovered on a lower level with the theoretical devices of other disciplines. The lower coil of the helix accommodates the complementary argumentations of anthropology and lexical semantics; the higher one brings the conclusions to the plane of discourse analysis and semiotics